PROCESSING ORGANIC WASTE INTO ECO ENZYME THROUGH P5 ACTIVITIES AT JUNIOR HIGH SCHOOL 1 MALEBER - Naila Az Zahra; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
Organic waste management in schools is an important issue in facing environmental challenges in Indonesia. This study aims to analyze the processing of organic waste into eco enzyme through the activities of the Pancasila Student Profile Strengthening Project (P5) at Junior High School 1 Maleber. This research uses a Participatory Action Research (PAR) approach, involving students in the process of planning, implementing, and evaluating activities. The results showed that this activity succeeded in increasing students' awareness of the importance of organic waste management, as well as strengthening the dimensions of the Pancasila Student Profile, especially in the aspects of mutual cooperation, independence, and critical reasoning. Hands-on practice in organic waste processing not only provides knowledge about fermentation, but also forms a caring attitude towards the environment. Evaluation showed positive changes in students' attitudes and understanding of waste management after participating in this activity.